Monocyte biology conserved across species: Functional insights from cattle - Talker, Stephanie C.; Barut, G. Tuba; Lischer, Heidi E.L.; Rufener, Reto; von Münchow, Lilly; Bruggmann, Rémy; Summerfield, Artur (Frontiers in Immunology, 2022)
Similar to human monocytes, bovine monocytes can be split into CD14highCD16- classical, CD14highCD16high intermediate and CD14-/dimCD16high nonclassical monocytes (cM, intM, and ncM, respectively). Here, we present an in-depth analysis of their steady-state bulk- and single-cell transcriptomes, highlighting both pronounced functional specializations and transcriptomic relatedness. Bulk gene transcription indicates pro-inflammatory and antibacterial roles of cM, while ncM and intM appear to be specialized in regulatory/anti-inflammatory functions and tissue repair, as well as antiviral responses and T-cell immunomodulation. Notably, intM stood out by high expression of several genes associated with antigen presentation. Anti-inflammatory and antiviral functions of ncM are further supported by dominant oxidative phosphorylation and selective strong responses to TLR7/8 ligands, respectively. Moreover, single-cell RNA-seq revealed previously unappreciated heterogeneity within cM and proposes intM as a transient differentiation intermediate between cM and ncM.